Sideways stories from Wayside School - Sachar, Louis, 1954- (Sachar, Louis, 1954- Wayside School series., 1990)
Humorous episodes from the classroom on the thirtieth floor of Wayside School, which was accidentally built sideways with one classroom on each story.